Study of the Effects of Climate Change on Surface Water Resources in the Ba River Basin - Thi Thu Ha, Pham; Duc Thien, Tran; Dieu Xuan, Nguyen; Ngoc Bach, Duong; Vu Trung Kien, Nguyen; Duc Tai, Nguyen; Minh Loan, Luu (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study assessed the impact of climate change on surface water resources at selected sites within the Ba River Basin, Vietnam. This research used the MIKE NAM hydrological model to assess surface water resources in the Ba River Basin. A parameter set is developed for the model to evaluate the current discharge of surface water and to simulate flows for future periods. Incorporating climate change scenarios for Vietnam provided by the Ministry of Natural Resources and Environment in 2020, the study reveals that mean annual streamflow across all sub-basins of the Ba River is likely to increase in all future periods relative to the baseline (1986-2005), with greater increases under RCP4.5 compared to RCP8.5. In the mid-21 st century (2046-2065), projected changes of flows range from 13% to 15%, while in the late 21 st century period (2080-2099), the annual flow variations range from 7% to 17%, with the largest increases projected in the late 21 st century under RCP4.5 scenario. The simulation results indicate a prolonged dry season with low water levels, while the flood season ends earlier with higher water discharge, increasing the variability between the two seasons. Especially during the dry season, the flow discharge decreases in the late 21 st century (2080-2099), with the reduction of -0.8% at An Khe station, -2% at Ayun Pa station, -1% at Cung Son station, and -2% across the entire basin compared to the baseline period (1986-2005). The findings of this study provide a scientific basis for supporting integrated water resources management, strategic planning, and sustainable exploitation of surface water resources in the Ba River Basin under climate change.